Bureaucracy Amid Political Power Struggle: A Critical Paradigmatic Review - Budiman, Arif; Yuwanto, Yuwanto; Nurhidayat, Nurhidayat; Alfirdaus, Laila Kholid (Ajudikasi : Jurnal Ilmu Hukum, 2024)
The study of bureaucracy politicization in Indonesia has been mainly putting bureaucracy on its passive-position scenes. It viewed civil servants as politically subordinated by political officials. Bureaucracy in this classic paradigm had no other role but to execute what political officials decided. The barrier was clear, politicians made policy; civil servants administered the policy. Politicians made decision; bureaucrats merely implemented them. In this kind of relationship, bureaucracy had no other option but to obey the political leader’s decisions submissively. This article came up with different perspectives. It criticized the classic paradigm and challenged the notion of civil servant’s subordination before politics. Applying literature review, this study found out that bureaucracy had not merely administered the policy but also engaged in the making of it. Bureaucrats had more than enough of authorities to may choose independently to either take passive-position as an object of politicization or becoming active political actor on the stage of political power competition. Considering more bureaucracy leaders transforming into political officials, this may lead to the re-establishment of bureaucratic polity in Indonesia in the near future.